Pengaruh Harga, Kualitas Produk, dan Promosi Terhadap Kepuasan Konsumen Pengguna Telkomsel di Kabupaten Badung - Eka Sugiantari Putu; Ayu Sudha Sucandrawati Ni Luh Ketut; Indiani Ni Luh (CV. Ulil Albab Corp, 2024)
This study aims to analyze and test the influence between the variables studied in this study. The effects tested include the effect between price, product quality and promotion on customer satisfaction of Telkomsel users in Badung Regency. The type of research used in this research is a survey with a data measurement tool, namely a questionnaire using a quantitative approach. The sample size in this study was 105 Telkomsel users who live in Badung Regency. The data collection method in this study used a questionnaire. The measurement scale used in this study is a Likert scale. The data analysis technique in this study is descriptive statistical analysis, multiple liner regression, and hypothesis testing. The data in this study were processed using SPSS 27.0 for Windows. Based on the t test results, the Price variable (X1) has a significance value of 0.047 which means <0.05. It can be concluded that partially the price (X1) has a positive and significant effect on customer satisfaction (Y) Telkomsel. Product quality (X2) has a significance value of 0.044 which means <0.05. It can be concluded that partially product quality (X2) has a significant and positive effect on customer satisfaction (Y) Telkomsel, the Promotion variable (X3) has a significance value of 0.041 which means <0.05. It can be concluded that partially promotion (X3) has a significant and positive effect on customer satisfaction (Y) Telkomsel. Based on the results of the F test, it shows that the F-count value is obtained at 3,965 with a significance level of 0.039. This means that there is a positive and significant influence together between promotion (X1), product quality (X2) and price (X3) work on customer satisfaction (Y) Telkomsel.